1995
DOI: 10.1021/ja00106a068
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Fulleroid to Methanofullerene Conversion via the Di-.pi.-methane (Zimmerman) Rearrangement

Abstract: . (1995). Photochemical fulleroid to methanofullerene conversion via the di-pi-methane (Zimmerman) rearrangement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
80
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(88 citation statements)
references
References 1 publication
8
80
0
Order By: Relevance
“…One is a direct [5,6]-ring closure to give [5,6]-open- [5,6]-closed 14 (path 1). Secondly, [5,6]-ring closure followed by a 1,5-sigmatropic shift in a similar manner to that found in the di-p-methane rearrangement [10] to form the [5,6]-open-[6,6]-closed fulleroid. In this case there are two possibilities.…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…One is a direct [5,6]-ring closure to give [5,6]-open- [5,6]-closed 14 (path 1). Secondly, [5,6]-ring closure followed by a 1,5-sigmatropic shift in a similar manner to that found in the di-p-methane rearrangement [10] to form the [5,6]-open-[6,6]-closed fulleroid. In this case there are two possibilities.…”
Section: Resultssupporting
confidence: 57%
“…[8] The pioneering works of Wudl, Diederich, and others [9] have shown that from the addition of carbene transfer reagents, such as diazo compounds to C 60 , [5,6]-open fulleroids were obtained as the kinetic products, which underwent rearrangement to give the thermodynamically stable [6,6]-closed methanofullerenes. Indeed this conversion was found to occur photochemically, [10] electrochemically, [11] and under acid catalysis. [12] Wudl proposed a di-p-methane rearrangement [10] in the photochemical conversion of the [5,6]-open fulleroid 9 to the [6,6]-closed methanofullerene 10.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Singlet energy transfer to low lying states of C 60 and the fullerene derivatives can occur, but their high rate for intersystem crossing would produce the metastable fullerene triplet states that have been observed previously using PIA and direct excitation of these acceptors. 14 The absence of the triplet PIA bands at 1.65 eV for BeCHA-PPV:C 60 and at 1.73 eV for BeCHA-PPV:͓5,6͔PC 61 BM or BeCHA-PPV:͓6,6͔PC 61 BM, however, is at variance with both singlet and triplet energy transfer.…”
Section: B Photoexcitation Of Composite Filmsmentioning
confidence: 97%
“…Hence, we cons i dered tha t the main product s hould be fulleroid-a 2, fol lowed by fulleroidb 3 a nd the mi nor product ful l eroi d -c 4. It i s wel l -known tha t ful leroids isomerize to methanofullerenes ([6,6]-closed derivatives ) through a di--methane rea rra ngement by the a cti on of l i ght or hea t. 11 Thus, three different [6,6]-cl os ed site-i s omers s houl d be formed a fter the i s omeri za ti on proces s . When the fulleroi ds fra cti on wa s i rra di a ted a t 360nm for 4h a t room temperature, the i s omeri za ti on from ful l eroi ds 2-4 to the [6,6]-PC71BM i s omers (5, 6 a nd 7, Scheme 2, Fi gure S26, S.I.)…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%